2015
DOI: 10.1111/deci.12158
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making and the Price Setting Newsvendor: Experimental Evidence

Abstract: We present an experimental study of the price‐setting newsvendor problem, which extends the traditional framework by allowing the decision maker to determine both the selling price and the order quantity of a given item. We compare behavior under this model with two benchmark conditions where subjects have a single decision to make (price or quantity). We observe that subjects deviate from the theoretical benchmarks when they are tasked with a single decision. They also exhibit anchoring behavior, where their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…The early single-period coordinating inventory and pricing control models include Mills (1959, 1962), Karlin and Carr (1962), Zabel (1970), Young (1978), Cheng (1984) and Hakan Polatog̈lu (1991). Recent studies on single-period models include Kocabıyıkoğlu et al (2016) and Serel (2017). One stream of literature focuses on multi-period models under the backorder setting.…”
Section: Discussionmentioning
confidence: 99%
“…The early single-period coordinating inventory and pricing control models include Mills (1959, 1962), Karlin and Carr (1962), Zabel (1970), Young (1978), Cheng (1984) and Hakan Polatog̈lu (1991). Recent studies on single-period models include Kocabıyıkoğlu et al (2016) and Serel (2017). One stream of literature focuses on multi-period models under the backorder setting.…”
Section: Discussionmentioning
confidence: 99%
“…We have chosen this form of a demand function with higher self‐price elasticity and lower competitor‐price elasticity for its simplicity and also because this form is broadly used in environments where two competing products coexist in a market where both of their prices affect the demand of each (Chen et al, 2013; Dan et al, 2012; Park et al, 2020). The price ranges and capacity values are also chosen in accordance with earlier literature (e.g., Akbay & Ayvaz Cavdaroglu, 2021; Kocabıyıkoğlu et al, 2016).…”
Section: Experimental Design and Methodsmentioning
confidence: 99%
“…The authors stated that revenue management allocation decisions are consistently larger than orders received from the newsvendor and argue that this is due to differing perceptions of subjects regarding overage and underage costs depending on the framing of the problem. Kocabıyıkoğlu et al (2016) focused solely on the price‐setting newsvendor problem and compared the decisions of the subjects when they are either entrusted with the single task of quantity allocation or with multiple tasks of pricing and quantity allocation. They found evidences of anchoring on expected demand for quantity decision, and anchoring on the initial inventory for the pricing decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a comparison of decision making of American and Chinese decision makers, Feng et al (2011) found that cultural aspects may have an additional influence on the pull-to-center effect. Other works in this research stream are those of Kocabykoglu et al (2016), Schiffels et al (2014) and Moritz et al (2013), among others.…”
Section: Single Selling Season Modellingmentioning
confidence: 99%